A new terrestrial species of Chiropterotriton (Caudata: Plethodontidae) from central Mexico - García-Castillo, Mirna G.; Rovito, Sean M.; Wake, David B.; Parra-Olea, Gabriela (Zootaxa, 2017)
Chiropterotriton is a relatively small genus that comprises 15 species with great morphological and ecological diversity. In previous studies, molecular data provided evidence for a considerable number of species that remain undescribed. In this study, we describe one new species, Chiropterotriton chico sp. nov. based on molecular and morphological characters. We present mtDNA phylogenetic analyses using Bayesian inference and maximum likelihood that include all described and several undescribed species. Morphometric data from eight recognized species provide evidence for the distinctiveness of the new taxon. Description of this new species adds to the already high salamander diversity of the state of Hidalgo, which is an important area for the diversification of the genus.